2023
DOI: 10.3390/microorganisms11010188
|View full text |Cite
|
Sign up to set email alerts
|

Possible Third Step Preventing Conjugation between Different Species of Blepharisma

Abstract: In the genus Blepharisma, reproductive isolation between different species appears to be established at least by two barriers: (1) a mating pheromone, i.e., gamone 1, and (2) a factor involved in pair formation. Using four species, we experimentally investigated other potential barriers to interspecific conjugation in Blepharisma, as well as the first and second barriers. Cell-free fluid from type I cells (CFF1) of B. americanum had no effect on B. undulans, B. japonicum, or B. stoltei. Type II cells of B. ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our research on interspecies conjugation revealed at least three essential steps for completion: (1) the gamone 1-mediated step (inducing mating pairs in type II cells), (2) assessing the formation of mating pairs by activated cells, and (3) producing offspring [ 23 , 24 ]. Essentially, gamone 1 exhibits species specificity; even within the same megakaryotype, it does not function across species (e.g., B. americanum and B. musculus , both belonging to Mk3, do not interact with each other) [ 22 , 23 , 24 ]. This implies that reproductive isolation essentially occurs at Step 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our research on interspecies conjugation revealed at least three essential steps for completion: (1) the gamone 1-mediated step (inducing mating pairs in type II cells), (2) assessing the formation of mating pairs by activated cells, and (3) producing offspring [ 23 , 24 ]. Essentially, gamone 1 exhibits species specificity; even within the same megakaryotype, it does not function across species (e.g., B. americanum and B. musculus , both belonging to Mk3, do not interact with each other) [ 22 , 23 , 24 ]. This implies that reproductive isolation essentially occurs at Step 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, a situation might occur where different species cohabit the same location, suggesting the potential for type II cells activated by the same species of gamone 1 to encounter activated type I cells and form mating pairs. We have reported on interspecies mating pair formation among artificially activated cells [ 23 , 24 ]. Yet, even when cells treated with gamone 1 of the same species are brought together, interspecies mating pairs are scarcely formed (e.g., between B. undulans (Mk2) and B. japonicum (Mk4), and between B. undulans (Mk2) and B. americanum (Mk3)), while in some cases, interspecies mating pairs are formed (e.g., between B. americanum (Mk3) and B. japonicum (Mk4) or between B. americanum (Mk3) and B. stoltei (Mk4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations